Technology interventions for enhancing the productivity and profitability of small holder agriculture in Vikarabad district of Telanagana: Technology interventions for enhancing the productivity and profitability of small holder agriculture in Vikarabad district of Telanagana - V JHANSI RANI; S V RAMANA RAO; A AZIZ QURESHI (Journal of Oilseeds Research, 2020)
The present study is based on technology interventions implemented under the Farmers FIRST Programme (FFP) on small holder agriculture in Vikarabad district of Telangana. Data from 30 households through random sampling was analysed for working out the profitability and B:C ratios for the interventions in oilseeds and pulses. The results suggest that the interventions led to increasing profitability through reduced cost of cultivation and increased productivity indicating higher B:C ratios due to technology interventions.